Analisis Nilai Tambah Dan Keuntungan Nilai Tambah Pengolahan Buah Salak Menjadi Salak Di Desa Werdhi Agung Selatan Kecamatan Dumoga Tengah Kabupaten Bolaang Mongondow - Palota, Chelin Rusandi; Loho, Agnes Estephina; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
This study aims to calculate the amount of added value and profit from processing snake fruit into snake fruit chips. The research was carried out from June to August 2022 in Werdhi Agung Selatan Village. The data used in this study are primary data obtained through observation, interviews, and recording of the results of interviews with business owners based on a prepared questionnaire. Secondary data is obtained from the literature and literature through documents, publications, or research results from various institutions or institutions that support and relate to the research topic. The data obtained were analyzed using added value analysis according to the hayami method. Based on the results of the research, the Mount Lanying IKM Home Industry business requires 40 kg of raw salak fruit in a day to produce 4 kg of salak chips. In 1 Kg of salak chips can produce 13 packs of chips so that in 4 Kg of chips you will get 52 packs of chips. The output price is IDR 17,000/pack with a weight of 75 grams. The added value obtained from processing snakefruit into snakefruit chips is IDR 4,907/Kg with a profit of IDR 2,407/Kg.